Optimizing surgical antimicrobial prophylaxis through clinical pharmacist-led audit and feedback: Evidence from a Vietnamese tertiary hospital - Dua Thi Nguyen; Son Ngoc Tran; Thu Thi Huyen Nguyen; Thuy Thi Thu Tran; Long Duc Nguyen; Trang Hoang Quynh Nguyen; Hao Trong Nguyen; Shukry Zawahir; Hai Thanh Nguyen; Thuy Thi Thu Nguyen; Van Thi Thuy Pham; Minh Duong Anh Vu; et al. (PLoS ONE, 2026)
The inappropriate use of surgical antibiotic prophylaxis (SAP) remains a common issue in Vietnam, posing a significant risk of surgical site infections (SSIs) and other adverse outcomes. This study aimed to evaluate the impact of a pharmacist-led audit–feedback (A&F) intervention, as part of an antimicrobial stewardship (AMS) program, on improving compliance with SAP guidelines. A prospective pre–post interventional study was conducted in the surgical departments of Saint Paul General Hospital. A multidisciplinary team, led primarily by clinical pharmacists, conducted audit–feedback activities on SAP practices from December 2023 to April 2024. The primary outcome was the overall compliance rate with SAP guidelines. Secondary outcomes included compliance with specific components: antibiotic selection, timing of administration, dosing, and duration of use. A total of 162 patients in the pre-intervention group and 147 in the post-intervention group were included. After two audit–feedback phases, overall compliance with SAP guidelines significantly increased from 60.49% to 76.87% (OR: 2.97, 95% CI: 1.71–5.28). Notably, the most significant improvements were observed in the appropriateness of antibiotic selection and duration of use, increasing from 74.69% to 88.44% (OR: 2.57, 95%CI: 1.40–4.89) and 72.84% to 88.44% (OR: 2.82, 95% CI: 1.55–5.36), respectively. Conclusion, the audit–feedback intervention led by clinical pharmacists substantially improved compliance with SAP guidelines across several domains. This study provides pragmatic evidence from a tertiary hospital in Vietnam, demonstrating that audit–feedback is not only feasible but also impactful in resource-limited settings. Importantly, this approach could inform scalable AMS and infection prevention policies in other low-and middle-income countries.